2003
DOI: 10.1046/j.1365-2559.2003.01732.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow histopathology following cytoreductive therapy in chronic idiopathic myelofibrosis

Abstract: Therapy-related bone marrow lesions in IMF comprise a strikingly variable spectrum that may include aplasia with scleroedema and a patchy distribution of myelodysplastic haematopoiesis associated with progressive myelofibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…It is not unusual to encounter biopsies with mixed grades, especially in biopsies from patients on therapy. 36,37 We compared the concordance of fibrosis grading in baseline and samples to those taken from patients on therapy; such an analysis has never been reported before our knowledge. We found that there was significantly lower agreement in samples taken from patients on fedratinib therapy (P ¼ 0.023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not unusual to encounter biopsies with mixed grades, especially in biopsies from patients on therapy. 36,37 We compared the concordance of fibrosis grading in baseline and samples to those taken from patients on therapy; such an analysis has never been reported before our knowledge. We found that there was significantly lower agreement in samples taken from patients on fedratinib therapy (P ¼ 0.023).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evaluation of only three randomly selected hematopoietic areas (total area of 1.5 mm 2 ) may Fibrosis/cellularity grading in bone marrow generate a significant bias concerning objectivity, particularly in cases with heterogeneity of reticulin grade that require careful examination of the entire slide. 36,37 In addition, Teman et al 47 validated only the computer-assisted scoring of grades 2 and 3. If such computer-based system is to be employed in clinical practice, it is imperative that the scoring software also recognizes grades 0 and 1 for treatment efficacy assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the classical syndrome, a variant of GMT characterized by adipocyte hyperplasia has been described in postchemotherapy leukemia and myeloma patients and in patients with myelofibrosis treated with cytoreductive drugs [9,10,11,12]. Clinically, unlike the classical form, chemotherapy-associated GMT was acute in onset, transient and not associated with cachexia [9].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of other treatment modalities on BMF in PMF was evaluated in a multicenter observational study of 309 patients with PMF with long follow-up. The study included 822 bone marrow biopsy specimens obtained from patients at different stages of their disease [63]. Among patients who received busulfan, 15% had a regression in BMF, 49% were stable, and 36% had progressive BMF.…”
Section: Therapeutic Strategies That Target Bmf In Pmfmentioning
confidence: 99%
“…Among patients who received busulfan, 15% had a regression in BMF, 49% were stable, and 36% had progressive BMF. Five percent of patients treated with hydroxyurea had regression of their BMF, 55% remained stable, and 40 progressed as compared with 17%, 55%, and 39% of patients treated with interferon a-2b, respectively [63]. Several JAK-STAT inhibitors have been evaluated in PMF, polycythemia vera, and ET [64].…”
Section: Therapeutic Strategies That Target Bmf In Pmfmentioning
confidence: 99%